EFFECT OF ENVIRONMENTAL, SOCIAL, AND GOVERNANCE DISCLOSURE ON FIRM VALUE WITH PROFITABILITY MODERATION IN ENERGY COMPANIES LISTED ON IDX 2021-2024 - Dheyvanza Arsy Akbar; Inung Wijayanti; Wahidatur Rosyidah; Laras Rayi Saraswati; Yumeizy Syahputra (Ikatan Dosen Menulis, 2026)
This research aims to analyze the effect of environmental, social, and governance (ESG) disclosure on firm value, proxied by Tobin’s Q, with the profitability ratio proxied by the return on equity ratio (ROE) serving as a moderating variable. The data used in this research are secondary data, including financial statements, annual reports, and sustainability reports published by the companies. The sample comprises 60 observations selected through purposive sampling from energy-sector firms listed on the Indonesia Stock Exchange for the 2021–2024 period. This quantitative study employs a multiple linear regression with a random effects model (REM). The tests were performed using EViews 13. The results indicate that ESG disclosure has no effect on firm value, while the profitability ratio proxied by ROE has a positive and significant effect on firm value.